Validation of a Prediction Rule for Legionella Pneumonia in Emergency Department Patients - Bolliger, Rebekka (Open Forum Infect Dis, 2019)
We validated a clinical prediction rule for Legionella based on clinical parameters (dry cough, fever) and laboratory findings (C-reactive protein, lactate dehydrogenase, sodium, platelet counts) in 713 consecutive patients with community-acquired pneumonia. The Legionella Score performed well in estimating the likelihood for Legionella infection and thus may help to direct diagnostic and therapeutic decisions.